Meningkatkan Hasil Belajar Siswa Kelas VIII SMPN 6 Kediri dalam Menulis Puisi dengan Pengembangan Model AIT (Aku Ingin Tapi) - Sutirta, Eka (Jurnal Simki Pedagogia, 2021)
The process of learning Indonesian in Class VIII-A of SMPN 6 Kediri experienced several obstacles. The problem is that the teacher only gives assignments or asks students to write poetry without being accompanied by unclear instructions on how to write poetry. After the evaluation, it was found that 53% of students had complete KKM scores. The solution to overcome this problem is by applying the AIT Model. This model has three steps include: the use of names; specify name; and tell the name figure. The application of AIT (I want to but) poetry learning is done by means of collaboration/groups. This is done in order to grow honesty, participation, cooperation between students and groups. Writing AIT poetry (I want to but) using image media in collaboration with the following learning steps. Students work together in groups of 4-6 children. The teacher distributes pictures to each group. Each student in the group receives a piece of paper to write a poem on. Each group discusses to determine the appropriate title for the image obtained and the image is used as inspiration in writing poetry. Based on the results of the student posttest, it can be seen that in the pre-cycle there were 53% (18) students who completed the KKM. Then, in the first cycle there were 73.5% (25) students who completed the KKM. Then, in the second cycle, 82% (28) students completed the KKM. The success of the research in accordance with the success indicators obtained in the second cycle, which is more than 75% of students complete the KKM. So it can be concluded that writing poetry with the application of the AIT Model is able to improve student learning outcomes for Class VIII-A SMPN 6 Kediri in Indonesian language lessons. Poetry writing materials in the even semester of the 2019/2020 school year.